Research of the spatial aspects of using renewable energy sources for sustainable development of the territory - Agapova, Olena; Popovych, Nataliia; Shulika, Boris; Peresadko, Vilina; Fylenko, Vitalii (Technology audit and production reserves, 2018)
The object of research is renewable energy sources as the basis for the development of renewable energy in Ukraine. Problems in the implementation of objects in this industry are the need to apply measures for their safe operation and less profitability of renewable energy sources compared to traditional ones. This is due to the high cost of equipment and significant costs to ensure technological processes. Increasing the share of renewable energy sources in the total energy balance will require government subsidies to the industry. It has been proven that the application of the cartographic approach allows determining the optimal locations of renewable energy facilities from an economic point of view and taking into account a number of equally important factors, in particular, social and environmental impact. The next methods are used: cartographic – when applying modeling techniques for building maps of renewable energy resources; geo-informational – in the process of collecting and processing information about resources, objects and factors for the development of renewable energy; statistical – at the stage of calculating the energy potential of wind energy, solar energy, geothermal and hydrological resources. The maps for the above-mentioned renewable energy directions are presented, recommendations on the optimal areas for the construction of energy facilities are given on the example of Kharkiv region (Ukraine). So, location: wind power plants are recommended in Vovchansk, Kharkiv, Velykyi Burluk regions; solar power plants – in Blyzniuky, Pervomaiskyi, Balakliia, Izium, Lozova and Borova; geothermal power plants – in the south of Barvinkove and Blyzniuky, southeast of Izium, Borova and Lozova districts. Perspectives for locating small hydropower stations within the study area are sections of the Siverskyi Donets, Udy, Berestova, Mzha, Merla rivers. The dependence of the economic efficiency of wind, solar, geothermal energy and small hydropower facilities on factors such as: distance of transportation of energy raw materials and finished energy to consumers; heat loss; cost of investment in the construction of infrastructure (power lines, electrical substations, heating networks).